Unpacking Profit Stability: The Strategic Role of Credit Quality During COVID-19 - Cenda Bergiana; Sumiati Sumiati; Himmiyatul Amanah Jiwa Juwita (Sharia Economic and Management Business Journal (SEMBJ), 2026)
Background This study explores how Bank ABC managed increasing credit risk during the COVID-19 pandemic while maintaining credit quality and profitability. The research focuses on understanding the implementation of credit restructuring strategies, the roles of key stakeholders, and the development of an effective credit quality management model under crisis conditions. Method This study employed a qualitative research approach to obtain an in-depth understanding of credit restructuring practices at Bank ABC. Data were analyzed through organizational processes, stakeholder roles, and strategic responses related to credit quality management during the pandemic period. Results The findings indicate that credit restructuring was implemented comprehensively through the application of prudential banking principles, debtor prioritization, rigorous verification procedures, and flexible repayment schemes. Strong collaboration among the Middle Bucket, Collection & Recovery, and Capital Ebas & Asset Sales units significantly contributed to reducing non-performing loan (NPL) risk and maintaining capital stability. Furthermore, the implementation of early warning systems, collection negotiations, asset sales, and digitalized collection processes improved operational efficiency and supported organizational profitability during the crisis. Conclusion The study concludes that the success of Bank ABC in managing credit risk during the COVID-19 pandemic was driven by adaptive credit restructuring strategies, strong cross-functional collaboration, and effective risk mitigation practices. These findings highlight the importance of integrated credit quality management and organizational flexibility in sustaining financial stability and profitability during periods of economic uncertainty.